Família e escola : o que as crianças do 1º ano têm a dizer? - Maia, Denise da Silva (2019)
This study aimed to understand how school, family and the relations between the two are comprehended and signified by first year elementary school children of a public and a private school in Porto Alegre (RS, Brazil). Their speech, writing and reading were analysed. Research was based on Childhood Sociology, which considers children as social actors and competent subjects, whom both contribute to and suffer influence from their social environment. Focus groups were created, dialogues were recorded and transcribed, and the children created drawings and writings. Textual Discourse Analysis was used for the oral and written narratives of children; their drawings were analysed based on several theorists. 11 final categories have been found: family conceptions, family members, families’ meanings, roles and parts, other emerging themes; school’s parts, meanings and conceptions, schoolfamily relation meanings and perceptions. Family was defined by the children as a social group, based on union and on its configuration: they listed who was part of it. Family was also considered a value and a fundamental context for survival. Its role is to provide care, affection and mutual help and to enable intimacy. Adults would care (the mother being the main caretaker), while children and animals would play. School was conceived as a place with a determined architectural configuration and a specific identity. It was considered a children’s environment that interacts with the family. The children attributed positive meanings for school: it’s good and important to attend to it, besides mandatory. It’s a place to learn, play, have fun and make friends. They saw themselves as object and subject of the family-school relation, taking the role of relevant protagonists. By their perspective, the focus of this relation is to evaluate the child as a student. The children also expressed negative expectations regarding the communication between family and school. They perceived an alliance amongst the adults and believed that the tensions arising from the family-school relation impact children the most, which makes them more vulnerable. The children revealed being worried and afraid while facing interactions between family and school but were also hopeful for positive resolutions.